Uranium exports and non-proliferation: A policy coordination challenge - Hubbard, Christopher (2007)
My topic today is one which is currently exercising many minds, both in Australia and further afield, and its outlines are easily described. As always, however, the devil is in the detail, so my remarks today will inevitably be both reasonably straightforward in Australian nuclear policy terms and far more complex in their implications. The nuclear non-proliferation regime is under serious threat from a number of directions and sources in 2007. While Libya has finally renounced its nuclear weapons ambitions, North Korea continues spasmodic negotiations in Beijing on the status of its weapons program, having recently convinced the world that it is now in possession of operational nuclear explosive devices.